2006
DOI: 10.1179/135100006x116664
|View full text |Cite
|
Sign up to set email alerts
|

The effect of polyphenolic extract from pine bark, Pycnogenol®on the level of glutathione in children suffering from attention deficit hyperactivity disorder (ADHD)

Abstract: One month of Pycnogenol administration (1 mg/kg body weight/day) caused a significant decrease in GSSG and a highly significant increase in GSH levels as well as improvement of GSH/GSSG ratio in comparison to a group of patients taking a placebo. TAS in children with ADHD was decreased in comparison with reference values. Pycnogenol administration normalizes TAS of ADHD children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…40 Another study performed by Dvoráková et al revealed that pycnogenolan extract from the pine barkadministration decreased oxidized glutathione and TAS levels and increased reduced glutathione in children with ADHD. 21 Some studies have shown that oxidant levels are neither decreased nor increased in patients with ADHD. For instance, the activity of superoxide dismutase and cathalase, which are antioxidant enzymes, did not show significant differences between ADHD and control groups, but these studies did not clearly show the total oxidative balance, and they provided conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Another study performed by Dvoráková et al revealed that pycnogenolan extract from the pine barkadministration decreased oxidized glutathione and TAS levels and increased reduced glutathione in children with ADHD. 21 Some studies have shown that oxidant levels are neither decreased nor increased in patients with ADHD. For instance, the activity of superoxide dismutase and cathalase, which are antioxidant enzymes, did not show significant differences between ADHD and control groups, but these studies did not clearly show the total oxidative balance, and they provided conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…20 Similarly, Dvoráková et al determined that there are low total antioxidant levels in children with ADHD. 21 Low levels of oxidant nitric oxide (NO) have also been reported in children with ADHD. 22 Furthermore, it has been shown that malondialdehyde (MDA) is statistically significantly low in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…However, high levels of MDA have been observed in both adults [115,116] and children with ADHD [117], and increased plasma MDA and urinary 8-OHdG levels were found in children with ADHD compared to healthy children [118]. Another study has shown low total antioxidant levels in children with ADHD [119]. Furthermore, the SHR model showed an increase in ROS production in the hippocampus, cortex, and striatum [120].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 99%
“…74 Importantly, biomarkers of oxidative damage decreased in the treatment group compared with placebo, and this was associated with improvement in symptoms. [75][76][77] Further controlled studies are clearly warranted to investigate effects of Pycnogenol on ADHD symptoms in children.…”
Section: Pycnogenol and Adhdmentioning
confidence: 99%